Examining the Effects of Childhood Cancer on the Parental Subsystem: Implications for Parents and Health Care Professionals—Part 3. (November 2016) - Moules, Nancy J.; Estefan, Andrew; McCaffrey, Graham; Tapp, Dianne M.; Strother, Douglas
This article is the third part of a hermeneutic research study examining the impact of childhood cancer experiences on the parental relationship. In Part 1, we offered an exploration of the phenomenon with background literature; a description of the research question, method, and design; and finally a discussion of relationships that survived, thrived, or demised, with an emphasis on the notions of difference and trading. In Part 2, we furthered the interpretations to look at the complexities of issues such as teams, roles, focus, protection, intimacy, grieving, putting relationships on hold, and reclaiming them. In this article, we discuss the advice that the participants offered us and how that advice might have implications for other parents in similar situations and health care professionals working with families experiencing childhood cancer.